STUDY OF INTRODUCED TABLE VINE VARIETIES IN THE LOCALITY VRAPČIĆI (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
The aim of this work was to study the effect of pruning on the yield and quality of grapes of three table grape varieties Black Magic, Muscat Bleu and Alphonse Lavallee in Herzegovina. The research lasted three years (2011-2013), each variety had three varieties of pruning, and each variety had four repetitions. The load levels of the studs in this research were 28 (Variant I), 32 (Variant II) and 40 (Variant III) buds per vine. The most important indicators of fertility and quality of grapes of the tested varieties were measured. Research carried out at the site of Vrapčić in the Mostar vineyard shows that all three investigated varieties can be successfully grown at the mentioned site, although the meteorological conditions in the years of the research were less favorable than the multi-year average. For all analyzed parameters, the greatest influence on their values was the variety, as an experimental factor, followed by the year of the research, and the least variant of pruning. Based on all the obtained results, it can be concluded that the Alphonse Lavallee variety gives the best results in the area of Herzegovina.